2022
DOI: 10.1038/s41417-022-00507-9
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal cancer-associated fibroblasts expressing Junctional Adhesion Molecule-A are amenable to infection by oncolytic reovirus

Abstract: Gastrointestinal (GI) cancers are characterized by extensive tumor stroma that both promotes tumor progression and acts as a physical barrier for adjacent tumor cells, limiting the effect of current treatment modalities. Oncolytic virotherapy is currently investigated in clinical trials as a novel therapeutic agent for different malignancies of the GI tract, but it is largely unknown whether these viruses can also target the tumor stroma. Here, we investigated the tropism of two commonly studied OVs, adenoviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The results demonstrated that all oncolytic viruses significantly inhibited cell viability in organoid cultures. The tropism of two commonly used OV, adenovirus (Ad5-Δ24) and reovirus (R124 and jin-3), toward primary gastrointestinal fibroblasts derived from human esophageal, gastric, duodenal, and pancreatic carcinomas was studied [ 173 ]. Considerable cell death was observed in the majority of the fibroblast cultures infected with either R124 or jin-3 reoviruses, while Ad5-Δ24 did not induce cell death in the vast majority of fibroblasts tested.…”
Section: Methodological Options In Front Of Research On Anticancer Th...mentioning
confidence: 99%
“…The results demonstrated that all oncolytic viruses significantly inhibited cell viability in organoid cultures. The tropism of two commonly used OV, adenovirus (Ad5-Δ24) and reovirus (R124 and jin-3), toward primary gastrointestinal fibroblasts derived from human esophageal, gastric, duodenal, and pancreatic carcinomas was studied [ 173 ]. Considerable cell death was observed in the majority of the fibroblast cultures infected with either R124 or jin-3 reoviruses, while Ad5-Δ24 did not induce cell death in the vast majority of fibroblasts tested.…”
Section: Methodological Options In Front Of Research On Anticancer Th...mentioning
confidence: 99%
“…Consequently, therapeutic strategies targeting these cells have gradually emerged [ 20 , 21 ]. Recently, it was demonstrated that oncolytic mammalian orthoreovirus (reovirus) was able to infect and kill human untransformed CAFs isolated from several gastrointestinal tumour types in vitro , in contrast to an oncolytic derivative of HAdV‐C5 [ 16 ]. To investigate whether GoraVir does have the potential to infect and lyse CAFs, the pancreatic stellate cell line PS‐1 was exposed to GoraVir or HAdV‐C5 at high and low MOI and cell viability was determined at 6 days post infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, HAdV‐C5 showed minor cytotoxicity at MOI 10 (mean residual viability 80.6 ± 3.58%) and no cell killing at a lower MOI. To continue our exploration of GoraVir's ability to infect and kill CAFs, we exposed patient‐derived primary fibroblasts previously isolated from pancreatic cancer tissues [ 16 ] with GoraVir at MOI 10 and measured cell viability at 5 days post infection. Again, GoraVir was shown to induce cell killing in the majority of primary fibroblasts (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations